Especificação de requisitos para o desenvolvimento de um sistema de apoio à decisão para gestão de transportes públicos intermodais - João Nuno Lemos de Sousa (2020)
The world population has been increasing in recent years, leading to the growth of urban areas worldwide. This urban growth led to the expansion of urban areas, forcing people to move away from the center of population focus and points of interest, such as work and leisure areas. This distance leads to a greater need for displacement and distance between these points, thus increasing the levels of mobility in the urban area, in and out. Thus, transport has a high social-economic impact on the urban population and the environment, leading to the creation of policies that encourage the use of public transport in favor or private transport, since it consumes less energy and emits less polluting gases, taking into account the same number of passengers and the number of kilometers traveled by both. In order to encourage the use of public transport, it is necessary to analyze how the public transport service works, and its particularities, in order to improve the users' perception of their use and their daily experiences with them and consequently their use. To this end, the quality of service associated with public transport services and the eight associated criteria, defined by European standards, were studied. From this analysis, the most relevant and the ones wiht increased influence in the quality of service of public transport are presented. This quality of service is represented through the loop of the quality of service and the respectives gaps, between the various levels identified, taking into account booth perspectives, the user perspective, allowing the assessment of satisfaction, in view of the difference between the expected quality of service and the perceived one, and the perspective of the service operator, who evaluates the performance of the service in a more objective way. After analyzing the public transport service, decision support systems for public transport management and planning are presented, taking into account its components and the associated decision levels. This analysis allows the identification of the main functionalities of such system and the interested parties. Finally, in order to develop a complete, clear and rigorous requirements specification document for the posterior development of a decision support system, for the management and planning of intermodal public transport, taking into account the strategic and tactical decision levels, we applied concepts presented in the scope of Systems Engineering and Requirements Engineering. After the stakeholders identification and their needs, according to the proposed objectives to be achieved, these were transformed into system requirements. This specification document presents the functional requirements that describe the operation of the system, taking into account the five phases: (i) data collection, (ii) pre-processing, (iii) processing, (iv) evaluation, and (v) visualization, and the three components of a decision support system: (i) database, (ii) conceptual model, and (iii) interface, always respecting the activities and concepts presented in the scope of Requirements Engineering.